5G NR sub-THz fiber-wireless integrated systems using polarization multiplexing-multiband technique and self-polarization diversity scheme - Ming-Chung Cheng; Hai-Han Lu; Hsiao-Mei Lin; Stotaw Talbachew Hayle; Xu-Hong Huang; Wei-Wen Hsu; Yu-Chen Chung; Yu-Yao Bai; Kelper Okram; Jia-Ming Lu (Scientific Reports)
Abstract Fifth generation (5G) new radio (NR) fiber-wireless integrated systems using polarization multiplexing-multiband technique and self-polarization diversity scheme are successfully implemented. Polarization multiplexing-multiband technique is an effectual method to enhance the transmission capacity and spectral efficiency of systems. Self-polarization diversity scheme is an efficient scheme for polarization demultiplexing, in which an x-polarized (y-polarized) optical carrier with multiple x-polarized (y-polarized) optical signals can be detected using single-ended photodiodes. The transmission of 5G NR sub-terahertz (THz) signals through fiber-wireless integrated systems holds promise to afford high-speed and long-haul wired-wireless communications. It shows the robustness to achieve high aggregate data rates and lays the foundation to meet the evolving demands of future communication systems. Through an integrated medium of 20 km single-mode fiber, 1.6 km optical wireless, and 4/8/12 m 5G NR wireless, four 5G sub-THz 32-quadrature amplitude modulation-orthogonal frequency-division multiplexing signals at x- and y-polarizations are transmitted with good transmission performance in terms of low bit error rates and error vector magnitudes. The successful transmission of sub-THz signals at different carrier frequencies and polarizations over fiber-wireless integrated systems proves system’s ability to support cutting-edge 5G NR fiber-wireless integrated systems.